2003
DOI: 10.1258/13558190360468209
|View full text |Cite
|
Sign up to set email alerts
|

What predicts patients' interest in the Internet as a health resource in primary care in England?

Abstract: Access, demographics and, particularly, motivational factors all influence patients' interest in the Internet as a health resource. Proposals to encourage more widespread use of digital health information need to take account of this complexity and not deal with access issues alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 0 publications
4
40
1
Order By: Relevance
“…Although this runs contrary to some previous literature, 190,191 it might be explained by the fact that more proximal variables, such as technology confidence and beliefs about telehealth, had not been included in previous research. Indeed, when similar behavioural or motivational factors are assessed, other research is consistent with our findings in demonstrating the integral role, 209 or even superiority, 210 of these constructs over demographic variables, albeit in terms of using the internet alone. Furthermore, a systematic review concluded that focusing on patient factors alone, as the majority of research in this area has done, is probably not comprehensive enough to understand patient interest in using telehealth.…”
Section: Results In the Context Of Existing Researchsupporting
confidence: 89%
See 2 more Smart Citations
“…Although this runs contrary to some previous literature, 190,191 it might be explained by the fact that more proximal variables, such as technology confidence and beliefs about telehealth, had not been included in previous research. Indeed, when similar behavioural or motivational factors are assessed, other research is consistent with our findings in demonstrating the integral role, 209 or even superiority, 210 of these constructs over demographic variables, albeit in terms of using the internet alone. Furthermore, a systematic review concluded that focusing on patient factors alone, as the majority of research in this area has done, is probably not comprehensive enough to understand patient interest in using telehealth.…”
Section: Results In the Context Of Existing Researchsupporting
confidence: 89%
“…Whereas we asked respondents about technology confidence, it is interesting to note that other studies have used negative framing and asked about technology anxiety 211,212 or difficulty using the internet. 210 Nonetheless, these studies also showed the equivalent association between lower technology anxiety and heightened interest in using telehealth.…”
Section: Results In the Context Of Existing Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…While this runs contrary to some previous literature [21,22], it might be explained by the fact that more proximal variables, like technology confidence and beliefs about telehealth, had not been included in previous research. Indeed, when similar behavioral or motivational factors are assessed, other research is consistent with our findings in demonstrating the integral role [42], or even superiority [39], of these constructs over demographic variables, albeit in terms of using the Internet alone. Furthermore, a systematic review concluded that focusing on patient factors alone, as the majority of research in this area has done, is probably not comprehensive enough to understand patient interest in using telehealth [20].…”
Section: Discussionsupporting
confidence: 88%
“…While this approach was directly in line with the purpose of the research—to inquire about future interest in services that could be delivered by existing health care providers—it is difficult to know what types of applications respondents were thinking about when they gauged their interest in telehealth delivered via social networking websites, for instance. Moreover, it is likely that there is relationship between how frequently technology is used and technology confidence [38,39], and this relationship should be controlled for in future research. Finally, the large number of variables analyzed raises the possibility of type 1 error due to multiple comparisons.…”
Section: Discussionmentioning
confidence: 99%